Redox modulation of curcumin stability: Redox active antioxidants increase chemical stability of curcumin. Issue 3 (18th December 2015) - Nimiya, Yoshiki; Wang, Weicang; Du, Zheyuan; Sukamtoh, Elvira; Zhu, Julia; Decker, Eric; Zhang, Guodong
Abstract : A major problem to develop curcumin‐based therapeutics is its poor stability at physiological pH. In this study, we found that a series of redox active antioxidants with diverse chemical structures, including gallic acid, ascorbate (vitamin C), tert ‐butylhydroquinone (TBHQ), caffeic acid, rosmarinic acid, and Trolox (a water‐soluble analog of vitamin E), dramatically increased curcumin stability in aqueous buffer, suggesting a redox‐dependent mechanism involved in regulating curcumin stability. Abstract : Scope: Substantial studies have shown that curcumin, a dietary compound from turmeric, has beneficial effects on many diseases. However, curcumin rapidly degrades at physiological pH, making it difficult to interpret whether the observed actions of curcumin are from curcumin itself or its degradation products. Therefore, it is important to better understand the mechanisms involved in curcumin degradation and the roles of degradation in its biological actions. Methods and results: Here, we show that a series of redox active antioxidants with diverse chemical structures, including gallic acid, ascorbate (vitamin C), tert ‐butylhydroquinone (TBHQ), caffeic acid, rosmarinic acid, and Trolox (a water‐soluble analog of vitamin E), dramatically increased curcumin stability in phosphate buffer at physiological pH. When treated in basal cell culture medium in MC38 colon cancer cells, curcumin rapidly degraded with a half‐life of several minutes and showed a weak antiproliferative effect; co‐addition of antioxidants enhanced stability and antiproliferative effect of curcumin. Finally, co‐administration of antioxidant significantly increased plasma level of curcumin in animal models. Conclusion: Together, these studies strongly suggest that a redox‐dependent mechanism plays a critical role in mediating curcumin degradation. In addition, curcumin itself, instead of its degradation products, is largely responsible for the observed biological actions of curcumin.